PERAN PESANTREN DALAM MENGIMPLEMENTASIKAN LAYANAN BIMBINGAN KELOMPOK MELALUI KOMUNIKASI EDUKATIF - Army, M. Rizki; Jarnawi; Muttaqin, Reza (Program Studi Komunikasi dan Penyiaran Islam, 2025)
Pesantren (Islamic boarding schools) play a pivotal role in shaping students' character and moral behavior. However, recent years have seen a rise in negative behaviors among students, including lack of discipline, verbal bullying, and exposure to inappropriate content. This study aims to examine the implementation of group counseling services based on educational communication in reducing deviant behavior at Pesantren Modern Al-Manar, Aceh Besar. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that group counseling at the pesantren is conducted systematically through halaqah sessions, guided discussions, and reflective meetings with mentoring teachers. The approach emphasizes reflection, emotional support, and the internalization of Islamic values rather than punitive measures. Islamic teachings form the foundation of each session, incorporating lessons from the Prophet Muhammad’s character and the principles of tazkiyah (self-purification). While this model effectively mitigates negative behavior, challenges remain, particularly the shortage of trained facilitators and limited physical resources. The study concludes that a collaborative and religious-based group counseling approach serves as a relevant and adaptable character-building model that can be replicated in other Islamic educational institutions. These findings contribute to the development of contextual counseling practices in pesantren and offer practical insights for policy-making in character education grounded in local values and Islamic spirituality